Analisis Implementasi Deep Learning dalam Mewujudkan Kreativitas Siswa SDN Batang-Batang Daya II - M. Humam Maulana; Yeni Puji Astuti; Jamilah (Mataram University, 2026)
This study aims to analyze the implementation of deep learning in fostering students' creativity at SDN Batang-Batang Daya II. A qualitative approach with a descriptive research design was employed. Data were collected through interviews, observations, and documentation, and subsequently analyzed using descriptive qualitative analysis to provide a comprehensive understanding of how deep learning is implemented in classroom practices. The findings reveal that deep learning is implemented through student-centered learning planning, contextual learning activities, reflective practices, the application of Project-Based Learning (PjBL), and the development of students' critical thinking skills, with teachers serving as facilitators of the learning process. The implementation of these strategies encourages students to become more active, creative, confident in expressing their ideas, and capable of generating solutions to problems encountered during learning. Nevertheless, the implementation still faces challenges, particularly the differences in students' critical thinking abilities, which require teachers to adopt differentiated learning strategies that accommodate diverse learning needs. Furthermore, support from the school, parents, and adequate learning facilities plays a significant role in ensuring the successful implementation of deep learning. Overall, the findings indicate that the implementation of deep learning contributes to creating more meaningful learning experiences while supporting the development of students' creativity in elementary school.